TEACHERS' STRATEGIES IN INTERNALISING RELIGIOUS VALUES AMONG STUDENTS AT STATE JUNIOR HIGH SCHOOL 2, GAJAH LAMPUNG CITY - Sarwo Edi; Heri Cahyono; Muhammad Ihsan Dacholfany (International Journal of Teaching and Learning, 2025)
"The purpose of this research is to find out how Islamic education teachers' strategies in internalizing religious values to students, what the impact of implementing the internalization of religious values on students is, and what are the inhibiting and supporting factors in the internalization of religious values to students. The research method used is a qualitative method The data collection technique in this study uses observation, interviews, and documentation The results of the study show that teachers use habituation, example, supervision, advice, and punishment strategies to instil religious values, which have a significant impact on students, especially grade 8. Activities such as congregational prayers, reciting, and moral learning increase discipline and positive behaviour. Inhibiting factors include a lack of student awareness, environmental influences, the lack of parental roles, teacher board and housing conditions. Meanwhile, supporting factors include student awareness,  parental support, teacher board guidance.